INSTRUMEN TES UNTUK MENGUKUR KEMAMPUAN BERPIKIR MATEMATIS TINGKAT TINGGI SISWA SMA - Hugo Theo Kurniason; Sugiatno Sugiatno; Hamdani Hamdani (Universitas Tanjungpura, 2018)
AbstractThis study aims to develop a higher order thinking test instrument and explain the higher order thinking skill of students at class XI MIPA SMA Negeri 1 Pontianak. This research is in the form of research and development with the type of research is the instruments development. The higher order thinking test is developed through the define stage, that is front-end analysis, learner analysis, material analysis, compiling test specifications; the design stage, that is composing the pointers item, writing item, reproduction of limited tests; the development stage, that is one to one, qualitative analysis, conducting test run, quantitative analysis, revision, assembling test; disseminate stage, that is mass production. Based on the results of the item analysis, it was found that the higher order thinking test instrument conform the precision indicators, so that it can be used to measure the higher order thinking skill. Based on the results of student answers analysis, it is found that the higher order thinking skill of students at class XI MIPA SMA Negeri 1 Pontianak is on the medium criteria, both for indicators to analyze, evaluate, create, or as a totality. Keywords: Instruments Development, Higher Order Thinking Test Instrument, Higher Order Thinking Skill